Comparison of Return on Assets Ratio and Non-Performing Loans Between Conventional Banks and Sharia Banks (Study at PT. Bank BTPN Tbk and PT. Bank BTPN Syariah Tbk) - Hestiani, Dewi; Hasanuh, Nanu (Peneliti.net, 2023)
The purpose of this study is to identify variations in Non Performing Loan (NPL) and Return On Assets (ROA) performance between PT Bank BTPN Tbk and PT Bank BTPN Syariah Tbk from 2017 to 2021. The data for this study were gathered through descriptive research using information from the websites of the OJK, IDX, BPS, PT Bank BTPN, and PT Bank BTPN Syariah. The Time Series Method and the Cross Sectional Approach are the two data analysis techniques used. Even if PT Bank BTPN's NPL has seen changes in the ratio, the study's findings demonstrate that PT Bank BTPN's NPL performance is superior to PT Bank BTPN Syariah's NPL. PT Bank BTPN performs better in terms of ROA than PT BTPN Syariah, despite the fact that both banks have seen ups and downs, because it is better at making the most of its assets.